Mesenchymal Stem Cell Culture on Composite Hydrogels of Hydroxyapatite Nanoparticles and Photo-Crosslinking Chitosan - Alvarez-Barreto, J.; Márquez, K.; Gallardo, E.; Moret, J.; Benítez, N.; Meyer, M.; Marsiccobetre, S.; Zujur, D. (Revista Mexicana de Ingenieria Biomedica, 2017)
Chitosan (QT) is a biopolymer that has been used in widely used in bone tissue engineering applications, demons-trating great potential for that purpose. Therefore, the present study aims to develop an in situ crosslinking hydro-gel system, composed of chitosan and hydroxyapatite (HAP). Briefly, chitosan was modified, using carbodiimide chemistry, with lactobionic and azidobenzoic acid to make it soluble at physiological pH and photo-crosslinkable, respectively. The modified chitosan was mixed with HAP, in different proportions, and later exposed to UV light, yielding hydrogels. Mesenchymal stem cells, from rat bone marrow, were seeded onto the hydrogels and cultured for 4, 10 and 16 days, under osteogenic and non-osteogenic conditions. Through cell proliferation and alkaline phosphatase activity assays, and confocal microscopy, it was observed that the majority of formulations supported cell adhesion and proliferation, and a significant early osteogenic differentiation in formulations 70:30 and 50:50, QT:HAP. According to these results, the proposed photo-crosslinking system has potential for tissue engineering applications, and further specific studies are proposed for cell differentiation.